A Profile of Organophosphorus Poisoning in Central Terai Region of Nepal: A Hospital Based Cross Sectional Study - Sah, Sanjay Kumar; Sah, Bishal; Ranpal, Bishwanath (Med Phoenix, 2024)
Introduction: Poisoning is the second most common method of suicide in Nepal. About 24% of poisoning death occurs as a result of ingestion of organophosphorus compounds. The present study shows sociodemographic as well as clinical profile of organophosphorus poisoning presenting to the emergency department of a tertiary center in mid-southern region of Nepal. Materials and Methods: Descriptive cross-sectional study was carried out among 108 (44 male and 64 females) patients attending the emergency department of National Medical College Teaching Hospital. Consent has been taken from the patient or their guardians before their recruitment in the study. The data were collected by using proforma. Statistical analysis was performed using SPSS 23.0 Results: The present study shows organophosphorus poisoning are more common among females. Most common age group is 21-30. Majority of patients (32.4%) were from lower middle class. Students are commonly involved in organophosphorus poisoning which was about 38.9% followed by farmers. Majority of the victims (43.5%) consumed poisoning due to family issues. Most common intent of poisoning was suicidal. Majority of victims (65.7%) predominantly showed the muscarinic signs. Most of the victims (38.9%) arrived between 4-10 PM. Route of administration of poisoning was oral in majority of cases (92.6%). Most common compound used by victims was Methyl parathion (34.3%). Conclusion: Organophosphate poisoning is common in female, farmer and students. Most common issue for suicide is family issue so proper psychological management and counselling should be provided to the venerable age group.